Hubungan Karakteristik Sosial dan Perilaku Ibu terhadap Keputusan Pemberian Susu Formula pada Bayi Usia 0-24 Bulan di Puskesmas Merdeka, Kota Bogor: Faktor-Faktor yang Berhubungan dengan Keputusan Ibu dalam Pemberian Susu Formula pada Bayi Usia 0-24 Bulan di Puskesmas Merdeka, Kota Bogor - Salsabilla, Alya; Anwar, Khoirul; Syah, Muh. Nur Hasan (Amerta Nutrition, 2023)
Background: Infants aged 0-24 months are known to experience a period of rapid growth and development with increasing vulnerability to deficiency and overnutrition. The low prevalence of exclusive breastfeeding among this age group is inversely proportional to the increasing trend of formula feeding motivated by several factors. Objectives: This study aimed to analyze the social factors affecting the decision of mothers to provide formula milk to infants aged 0-24 months. Methods: A quantitatively descriptive method with a cross-sectional design was used, while the respondents were mothers having infants aged 0-24 months and were active in visiting the health center. The respondents totaled 66 people who were further divided into groups including mothers who provided formula milk and those who did not. The sample selection was achieved with the purposive sampling method, while data were collected by distributing questionnaires on several factors which had responses ranging from never to frequently. Results: The results showed that there were differences in the variable role of health workers between formula and non-formula milk groups with a significance value of 0.014 (<0.05). Moreover, there was a significant relationship between family support (P=0.002; R=0.373) and the role of health workers (P=0.001; R=0.387) in the decision to provide formula feeding. Conclusions: There was no significant difference in the nutritional status of infants who were provided formula milk and those who were not. On the other hand, a significant relationship was found between family support and the role of health workers in formula feeding of infants 0-24 months. Other variables such as maternal knowledge of breast milk, early initiation of breastfeeding, and promotion of formula milk had no significant association with formula feeding.